Molecular Phylogenetic Analysis of 16S rRNA Gene of Facultative Hetero-Fermentative Lactic Acid Bacteria - Habib Ramadhan; Erna Wulandari (Biology, Medicine, & Natural Product Chemistry, 2026)
Facultative heterofermentative lactic acid bacteria are bacteria that ferment carbohydrates to produce lactic acid and by-products such as acetic acid, ethanol, and CO2. This group of bacteria is widely used in the food and health industries. However, research on BAL species, especially the facultative heterofermentative group, is still relatively limited, so further studies are needed with molecular phylogenetic analysis aimed at providing an overview of the kinship of BAL species in the facultative heterofermentative group using the 16S rRNA gene molecular marker for more accurate identification results. The research design was conducted as a molecular-based descriptive analysis using secondary data in the form of 16S rRNA gene nucleotide sequences taken from the National Center for Biotechnology Information (NCBI) GenBank. Data analysis was performed using bioinformatics tools, including sequence alignment using ClustalX, phylogenetic tree reconstruction using MEGA and PHYLIP, and similarity matrix analysis using PHYDIT. The results of the analysis showed that Lactobacillus casei and Lactobacillus rhamnosus, as well as Lactobacillus pentosus and Lactobacillus plantarum, were closely related with a bootstrap value of 100% and a similarity matrix of 98-99%. Meanwhile, Lactobacillus alimentarius showed a relatively close relationship with Lactobacillus pentosus and Lactobacillus plantarum with bootstrap values and similarity matrices of around 92%. Thus, molecular phylogenetic analysis is effective in analyzing, identifying, and proving the relationship between BALs of the facultative heterofermentative group.